Can polygonal faults help locate deep-water reservoirs? - Jackson,CAL; Carruthers,TD; Mahlo,S; Briggs,O (AAPG Bulletin, 2014)
Polygonal faults are compaction-related normal faults that develop in very fine-grained sedimentary successions. Despite their ubiquity, few studies have highlighted the application of polygonal fault mapping to identifying deepwater sandstone reservoirs. We use 3D seismic and borehole data from the Måløy Slope, offshore Norway to demonstrate that the distribution, cross-sectional geometry and throw characteristics of polygonal faults can be used to locate deepwater sandstone reservoirs. Two tiers of polygonal fault are identified in the Cretaceous to lower Palaeogene succession. The lowermost tier is stratigraphically restricted to the lower Barremian-to-lowermost Turonian succession and likely formed during the early Turonian. The uppermost tier is well-developed, spans the entire Cretaceous succession and likely formed during the Maastrichtian. An abrupt decrease in the thickness of the upper tier occurs where a 92 m thick, sandstone-rich slope fan is developed in the upper Turonian interval. Furthermore, the lower tips of faults in the upper tier, which are defined by anomalously high throw gradients, cluster at the top of the sandstone, resulting in decoupling of this tier from the underlying, early Turonian tier. We interpret that faults in the upper tier nucleated above the reservoir across the entire slope and that the slope fan sandstone acted as a mechanical barrier to downward fault propagation, resulting in abrupt thinning of the tier at the sandstone pinchout. Polygonal faults are not simply an academic curiosity; mapping of these enigmatic structures can have practical applications for the delineation of a variety of reservoir types in hydrocarbon-bearing sedimentary basins worldwide.